HUSt: a heterogeneous unified storage system for GIS grid - Zeng, Lingfang; Zhou, Ke; Shi, Zhan; Feng, Dan; Wang, Fang; Xie, Changsheng; Li, Zhitang; Yu, Zhanwu; Gong, Jianya; Cao, Qiang; Niu, Zhongying; Qin, Lingjun; et al. (Conference on High Performance Networking and Computing: Proceedings of the 2006 ACM/IEEE conference on Supercomputing; 11-17 Nov. 2006, 2006)
Geographic Information System Grid integrates geographic information systems and Grid technology for data gathering, accessing, transmitting and service, in different I/O patterns, built upon massive storage systems. Existing non-standardized multi-source and multi-scale data lack spatial information sharing either internally or externally between organizations or departments, especially in national or global applications. HUSt is a massive storage system that was built at Wuhan National Laboratory for Optoelectronics, in China. There are heterogeneous storage areas in the system, including Object-based Storage System for the main data storing especially for the data searched frequently, Virtual Interface based Storage System for the data required at high transfer speed, and InfiniBand based SAN for high performance. HUSt is primarily meant for research on the organization and key technologies of storage systems for the next generation Internet. The goal is to unify network storage and construct a peta-byte storage system, which supports GIS Grid and applications.